Answer:
(-4,3) it is x axis -4 and y axis 3
Answer:
11
3Step-by-step explanation:
Given
3(x - 1)² + 2x - 7 ← substitute x = 3 into the expression
= 3(3 - 1)² + 2(3) - 7
= 3(2)² + 6 - 7
= 3(4) - 1
= 12 - 1
= 11
Answer:
![true](https://tex.z-dn.net/?f=true)
![\huge\underline\pink{Hope\:that\:helps}](https://tex.z-dn.net/?f=%5Chuge%3C%2Fp%3E%3Cp%3E%5Cunderline%5Cpink%7BHope%5C%3Athat%5C%3Ahelps%7D)
mark the person below as brainliest !!
if x-2 is a factor of polynomial, f (×) ,then it means we can find the zeros or the solutions of the polynomial by putting for (×-2)=0 . Because the zeros or roots of a polynomial is found by putting f (×)=0 , where x is a factor of the polynomial